2016
DOI: 10.1007/s41465-016-0002-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Creative Thinking Skills Using a Cognitive-Based Creativity Training

Abstract: Creative thinking skills can be considered one of the key competencies for the twenty-first century-they allow us to remain flexible and provide us with the capacity to deal with the opportunities and challenges that are part of our complex and fast-changing world. The increased focus on innovation combined with recent reports of decrements in creative performance brings attention to the need to develop creative thinking skills at both the educational and business levels. The main objective of the current proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
143
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 217 publications
(161 citation statements)
references
References 41 publications
4
143
0
14
Order By: Relevance
“…Of further importance to our present study is the fact that creative thinking is not a hardwired virtue. Several behavioral studies have shown that the processes underlying creative thinking can be systematically enhanced and impaired by both behavioral interventions, such as meditation, as well as, psychopharmacological agents, as for instance cannabis, tyrosine, and Adderall (e.g., Baas et al 2014; Colzato et al 2015; Farah et al 2009; Kowal et al 2015; Ritter and Mostert 2016; Schafer et al 2012; Zabelina and Robinson 2010; Davis 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Of further importance to our present study is the fact that creative thinking is not a hardwired virtue. Several behavioral studies have shown that the processes underlying creative thinking can be systematically enhanced and impaired by both behavioral interventions, such as meditation, as well as, psychopharmacological agents, as for instance cannabis, tyrosine, and Adderall (e.g., Baas et al 2014; Colzato et al 2015; Farah et al 2009; Kowal et al 2015; Ritter and Mostert 2016; Schafer et al 2012; Zabelina and Robinson 2010; Davis 2009). …”
Section: Introductionmentioning
confidence: 99%
“…One model that can be used is Project-based learning, this model is very suitable because students will be asked to make a project and this is related to the realm of C6 (creating). Students will be trained to be creative and make things like products (Elif, 2016;Ichsan & Mulyani, 2018;Ritter & Mostert, 2017;Yang, Lee, Hong, & Lin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Future research may examine whether a combined use of intuitive and deliberative processing mode can further improve creative idea selection, and whether specific traits or states, manipulations and trainings (e.g., Nijstad et al, 2010;Ritter et al, 2012;Ritter & Mostert, 2016) can influence creative idea selection.…”
Section: Discussionmentioning
confidence: 99%